UKRAINE ETHNOGRAPHY OF FOREIGN: EXPERIENCE OF BOGDAN BORА - Cachcan, V. A. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In the article poetic creation of Bogdan Bora is analysed. the basic lines of his poetries are certain. filosofichnist is the most notable sign of his works. Activity of Bogdan Bora on pedagogical field is explored .